Drug-resistant colon cancer cells produce high carcinoembryonic antigen and might not be cancer-initiating cells - Lee HC; Ling QD; Yu WC; Hung CM; Kao TC; Huang YW; Higuchi A (Dove Medical Press, 2013)
Hsin-chung Lee,1,2 Qing-Dong Ling,1,3 Wan-Chun Yu,4 Chunh-Ming Hung,4 Ta-Chun Kao,4 Yi-Wei Huang,4 Akon Higuchi3–51Graduate Institute of Systems Biology and Bioinformatics, National Central University, Jhongli, Taoyuan, 2Department of Surgery, Cathay General Hospital, Da'an District, Taipei, 3Cathay Medical Research Institute, Cathay General Hospital, Hsi-Chi City, Taipei, 4Department of Chemical and Materials Engineering, National Central University, Jhongli, Taoyuan, Taiwan; 5Department of Reproduction, National Research Institute for Child Health and Development, Okura, Tokyo, JapanPurpose: We evaluated the higher levels of carcinoembryonic antigen (CEA) secreted by the LoVo human colon carcinoma cells in a medium containing anticancer drugs. Drug-resistant LoVo cells were analyzed by subcutaneously xenotransplanting them into mice. The aim of this study was to evaluate whether the drug-resistant cells isolated in this study were cancer-initiating cells, known also as cancer stem cells (CSCs).Methods: The production of CEA was investigated in LoVo cells that were cultured with 0–10 mM of anticancer drugs, and we evaluated the increase in CEA production by the LoVo cells that were stimulated by anticancer drug treatment. The expression of several CSC markers in LoVo cells treated with anticancer drugs was also evaluated. Following anticancer drug treatment, LoVo cells were injected subcutaneously into the flanks of severe combined immunodeficiency mice in order to evaluate the CSC fraction.Results: Production of CEA by LoVo cells was stimulated by the addition of anticancer drugs. Drug-resistant LoVo cells expressed lower levels of CSC markers, and LoVo cells treated with any of the anticancer drugs tested did not generate tumors within 8 weeks from when the cells were injected subcutaneously into severe combined immunodeficiency mice. These results suggest that the drug-resistant LoVo cells have a smaller population of CSCs than the untreated LoVo cells.Conclusion: Production of CEA by LoVo cells can be stimulated by the addition of anticancer drugs. The drug-resistant subpopulation of LoVo colon cancer cells could stimulate the production of CEA, but these cells did not act as CSCs in in vivo tumor generation experiments.Keywords: drug treatment, colon cancer cell, 5-fluorouracil, stem cell, CD133